2019
DOI: 10.1136/openhrt-2018-000989
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based cardiac rehabilitation for stable angina: systematic review and meta-analysis

Abstract: ObjectiveA systematic review was undertaken to assess the effects of exercise-based cardiac rehabilitation (CR) for patients with stable angina.MethodsDatabases (Cochrane Central Register of Controlled Trials, MEDLINE, Embase and CINAHL) were searched up to October 2017, without language restriction. Randomised trials comparing CR programmes with no exercise control in adults with stable angina were included. Where possible, study outcomes were pooled using meta-analysis. Grading of Recommendations Assessment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…However, for stable angina the level of evidence is quite low, due to limited randomized trials. 36 Despite a potential benefit, stable coronary patients and post elective PCI patients have lower participation (referral) rates than ACS, 37 especially in those with multiple risk factors and/or low functional capacity. Patient participation in cardiac rehabilitation remains far too low, particularly in women, the elderly and the socio-economically deprived.…”
Section: Ccssmentioning
confidence: 99%
“…However, for stable angina the level of evidence is quite low, due to limited randomized trials. 36 Despite a potential benefit, stable coronary patients and post elective PCI patients have lower participation (referral) rates than ACS, 37 especially in those with multiple risk factors and/or low functional capacity. Patient participation in cardiac rehabilitation remains far too low, particularly in women, the elderly and the socio-economically deprived.…”
Section: Ccssmentioning
confidence: 99%
“…Although the effects of exercise training in patients with angina are under reported [13], systematic reviews and meta-analyses conducted in 2011 and 2016 have reported that exercise-based CR reduces cardiovascular mortality and hospital admissions by up to 26 % and 18 % respectively, over 12 months in patients with CHD [7,14]. Nevertheless, the effect of exercise-based CR in the era of contemporary medical care has been brought in to question by a recent systematic review and meta-analysis of trials conducted after the year 2000 [15].…”
Section: Clinical Benefit Of Cardiac Rehabilitationmentioning
confidence: 99%
“…Different acute and chronic changes in autonomic regulation, cardiac metabolism, signaling pathways, and protein expression in exercising hearts leading to cardiac growth and cellular reprogramming have been discovered over recent years. Especially, the beneficial effects of sports in heart failure and stable angina pectoris on patient outcomes, hospital admission, quality of life, and exercise capacity have been demonstrated [9,10,11]. However, the exact mechanisms of how physical activity delays the development of cardiovascular diseases remain unclear.…”
Section: Introductionmentioning
confidence: 99%